Casein, whey protein and non-protein nitrogen content of milk to identify water, sugar and flour adulterated milk (Bangladesh Journal of Animal Science, 2024)
This study was aimed to assess the potential of using milk's nitrogen distribution pattern, specifically casein, whey protein, and non-protein nitrogen content, as a method for detecting milk adulteration with water, sugar, and flour. Whole milk samples were collected from the Bangladesh Agricultural University Dairy Farm, BAU, Mymensingh, and subjected to adulterations, including 15%, 20%, and 25% water additions and subsequent sugar or flour adjustments to match the fresh milk's specific gravity. The samples were analyzed for specific gravity, fat content, and nitrogen distribution. Results indicated that while specific gravity remained consistent across samples adulterated with sugar or flour, it varied significantly (P